Ameliorative effect of tocotrienols on perimenopausal-associated osteoporosis—a review - Gengfan, Liang; Siew, Audrey Foong Kow; Chau, Ling Tham; Yu, Cheng Ho; Ming, Tatt Lee (Multidisciplinary Digital Publishing Institute, 2022)
Osteoporosis, or bone loss, is a disease that affects many women globally. As life expectancy increases, the risk of osteoporosis in women also increases, too, and this will create a burden on the healthcare and economic sectors of a country. Osteoporosis was once thought to be a disease that would occur only after menopause. However, many studies have shown that osteoporosis may develop even in the perimenopausal stage. Due to the erratic levels of estrogen and progesterone during the perimenopausal stage, studies suggest that women are exposed to the risk of developing osteoporosis even at this stage. The erratic hormonal changes result in the production of proinflammatory mediators and cause oxidative stress, which leads to the progressive loss of bone-building activities. Tocotrienols, members of vitamin E, have many health-promoting properties. Due to their powerful anti-oxidative and anti-inflammatory properties, tocotrienols have shown positive anti-osteoporotic properties in post-menopausal studies. Hence, we propose here that tocotrienols could also possibly alleviate perimenopausal osteoporosis by discussing in this review the connection between inflammatory mediators produced during perimenopause and the risk of osteoporosis. Tocotrienols could potentially be an anti-osteoporotic agent, but due to their low bioavailability, they have not been as effective as they could be. Several approaches have been evaluated to overcome this issue, as presented in this review. As the anti-osteoporotic effects of tocotrienols were mostly studied in post-menopausal models, we hope that this review could pave the way for more research to be done to evaluate their effect on peri-menopausal models so as to reduce the risk of osteoporosis from an earlier stage.